The relationship between children's temperament, mothers' perceived stress and social and emotional development of preschool children from Malaysia urban low-income households - Khairuddin, Laili Harlina; Madon, Zainal; Arshat, Zarinah (Human Resource Management Academic Research Society, 2023)
It is well known that young children from low-income households are prone to develop social and emotional deficits. However, relatively little research has been conducted on preschool children from urban low-income households. This study's objective was to examine the relationship between children's temperament, mothers' perceived stress, and the social and emotional development of preschool children from low-income households in urban Malaysia. 360 mothers of preschool children aged 42 to 53 months, whose children attend Taska PERMATA KEMAS from low-income households in the Klang Valley, were assessed through a set of questionnaires to determine the relationship between the variables. Consistent with previous research, the results indicated that children who experience and exhibit more negative emotions and have a low ability to regulate their thoughts, emotions and behaviour tend to exhibit more deficits in their social and emotional development. In addition, mothers who experience more stress in their daily lives have children who display greater deficits in their social and emotional development. As this study is cross-sectional in nature, future studies should consider employing a longitudinal design to establish causality in the relationship. Additionally, adopting a multi-informant approach would provide a more comprehensive understanding of the relationship.